2013
DOI: 10.1007/s10722-013-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

“Facilitated access” to plant genetic resources: does it work?

Abstract: The International Treaty on Plant Genetic Resources for Food and Agriculture entered into force in 2004 and is an important instrument by which plant breeders can access crop genetic diversity on the basis of multilateral ''facilitated access''. To test how well access works, we sent seed requests to 121 countries that are Contracting Parties to the Treaty. Seeds were received from 44 countries, 54 countries did not respond, while for 23 countries contacts stopped for various reasons: loss of communication, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…Also, there is much ambiguity about the status of PGR not included in ex situ collections but occurring under in situ conditions. Bjørnstad et al (2013) tested the extent to which facilitated access was functioning in practice by sending requests for seeds to 121 countries which were Contracting Parties to the ITPGRFA. They received seeds from 44 of these countries, with 54 countries not responding and contacts with the other 23 countries not resulting in obtaining the seeds requested.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is much ambiguity about the status of PGR not included in ex situ collections but occurring under in situ conditions. Bjørnstad et al (2013) tested the extent to which facilitated access was functioning in practice by sending requests for seeds to 121 countries which were Contracting Parties to the ITPGRFA. They received seeds from 44 of these countries, with 54 countries not responding and contacts with the other 23 countries not resulting in obtaining the seeds requested.…”
Section: Discussionmentioning
confidence: 99%
“…Bjornstad et al (2013) reported that of seed requests sent to 121 countries, seeds were received from only 44 (36%). Contractual terms in the present standard material transfer agreement are currently under review by the governing body of the treaty.…”
Section: The Costs Of Acquiring Genetic Stocksmentioning
confidence: 99%
“…Nonetheless, significant improvements remain to be made regarding accessibility of germplasm from genebanks. Bjornstad et al (2013) reported that of seed requests sent to 121 countries, seeds were received from only 44 (36%). Additional germplasm may be available on a bilateral basis once countries have implemented biodiversity laws under the auspices of the Convention on Biological Diversity.…”
Section: The Costs Of Acquiring Genetic Stocksmentioning
confidence: 99%
“…These policy developments have, or rather have been discussed to have, an apparent effect on the germplasm exchange patterns of member countries which, otherwise, had been major donors for many international ex situ collections that are globally utilized in various crop breeding programmes. Whether or not ITPGRFA facilitated access to PGR is also still a mooted question [ 15 ].…”
Section: Introductionmentioning
confidence: 99%